Evidence of Diradicals Involved in the Yeast Transketolase Catalyzed Keto‐Transferring Reactions - Hsu, Ning‐Shian; Wang, Yung‐Lin; Lin, Kuan‐Hung; Chang, Chi‐Fon; Ke, Shyue‐Chu; Lyu, Syue‐Yi; Hsu, Li‐Jen; Li, Yi‐Shan; Chen, Sheng‐Chia; Wang, Kuei‐Chen; Li, Tsung‐Lin (Chembiochem : a European journal of chemical biology, 2018)
Transketolase (TK) catalyzes a reversible transfer of a two‐carbon (C2) unit between phosphoketose donors and phosphoaldose acceptors, for which the group‐transfer reaction that follows a one‐ or two‐electron mechanism and the force that breaks the C2“−C3” bond of the ketose donors remain unresolved. Herein, we report ultrahigh‐resolution crystal structures of a TK (TKps) from Pichia stipitis in previously undiscovered intermediate states and support a diradical mechanism for a reversible group‐transfer reaction. In conjunction with MS, NMR spectroscopy, EPR and computational analyses, it is concluded that the enzyme‐catalyzed non‐Kekulé diradical cofactor brings about the C2“−C3” bond cleavage/formation for the C2‐unit transfer reaction, for which suppression of activation energy and activation and destabilization of enzymatic intermediates are facilitated. Moving C2 units: Transketolase from P. stipitis catalyzes a reversible C2‐transfer radical mechanism, in which the thiamine diphosphate cofactor is subject to enzyme‐catalyzed isomerization to form non‐Kekulé diradicals required for bond cleavage/formation because of suppression of the activation energy and activation and destabilization of intermediates.